2023
DOI: 10.1039/d3dt00043e
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated bipyridyl-based Mn-MOFs with Lewis acid–base bifunctional sites for highly efficient catalytic cycloaddition of CO2 with epoxides and Knoevenagel condensation reactions

Abstract: Metal-organic frameworks (MOFs) have become preferred heterogeneous catalytic materials for many reactions due to their advantages such as porosity and abundant active sites. Here, a 3D Mn-MOF-1 [Mn2(DPP)(H2O)3]·6H2O (DPP =...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 76 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Adsorption experiments showed that the maximum adsorption capacity of CO 2 was 22.23 cm 3 /g (1 atm) at 273 K (Figure S60), indicating that Er-MOF had an affinity for CO 2 and contributed to the occurrence of the CO 2 cycloaddition reaction. In addition, the synergistic effects of Lewis acid and base sites were critical for the cycloaddition reaction of epoxides and CO 2 , so a plausible catalytic reaction mechanism was proposed. First, the Lewis acid site (Er center) polarizes the epoxide through the coordination interaction, and the activated epoxide is opened by Br – ions of TBAB as nucleophiles to form a metal-coordinated bromoalkoxide intermediate. Meanwhile, the Lewis base site (uncoordinated N atoms in the ligand) activates the CO 2 molecule, which then forms an alkylcarbonate anion with the ring-opened epoxide, and then it is converted to cyclic carbonate by an intramolecular ring-closing reaction, and regenerating the catalyst and cocatalyst can be used in the next cycle (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption experiments showed that the maximum adsorption capacity of CO 2 was 22.23 cm 3 /g (1 atm) at 273 K (Figure S60), indicating that Er-MOF had an affinity for CO 2 and contributed to the occurrence of the CO 2 cycloaddition reaction. In addition, the synergistic effects of Lewis acid and base sites were critical for the cycloaddition reaction of epoxides and CO 2 , so a plausible catalytic reaction mechanism was proposed. First, the Lewis acid site (Er center) polarizes the epoxide through the coordination interaction, and the activated epoxide is opened by Br – ions of TBAB as nucleophiles to form a metal-coordinated bromoalkoxide intermediate. Meanwhile, the Lewis base site (uncoordinated N atoms in the ligand) activates the CO 2 molecule, which then forms an alkylcarbonate anion with the ring-opened epoxide, and then it is converted to cyclic carbonate by an intramolecular ring-closing reaction, and regenerating the catalyst and cocatalyst can be used in the next cycle (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…64,65 Mainly, synthesis of cyclic carbonates from epoxides has attracted considerable attention because of their applications as fine chemicals in pharmaceutical industries, starting materials in polymer industries, electrolytes in battery industries, etc . 66,67 Over the years, zeolites, 68 porous-organic polymers (POPs), 69 coordination organic frameworks (COFs), 70,71 metal–organic frameworks (MOFs), 72–77 and nanoparticle supported materials 49–53,78 have been utilized for the conversion of epoxides to cyclic carbonates. Still, due to the chemical inertness of CO 2 , the utilized reaction conditions in these catalysts are relatively harsh.…”
Section: Introductionmentioning
confidence: 99%